State Plan for 1960-61 List of Schemes Showing Outlay and Central Assistance Government of Madras - Planning Commission (Planning Commission, 1960)
This list has been prepared generally on the basis of the outlay as budgeted in the State’s Budget for 1960-61 and a few subsequent alterations intimated by the Heads of Departments. the assistances duo have been calculated for this outlay and on the basis of the approved pattern.
Government of Madras, Finance Department